The Relationship of Personal Traits and Alienation of Students with Disabilities - Tretyak E.V (Moscow State University of Psychology and Education, 2021)
The article deals with the problem of alienation from academic work among students with disabilities, as well as the relationship of alienation from study and personal characteristics. The relevance lies in the need to study the alienation from study of students with disabilities due to the fact that they are at risk for academic failure due to the difficulties that arise during training in conditions of the need for inpatient treatment and the need for special equipment. The purpose of the article is to determine the relationship of personal characteristics and alienation of students with HIA. The sample consisted of students of the Moscow State Psychological and Pedagogical University (N=75; respondents aged 20 to 25 years (M=22.6, SD=2.5), of which 88% of respondents were female). All students have the status of "limited health opportunities" (cerebral palsy, visually impaired, hearing impaired, having chronic kidney diseases and autoimmune system). Data collection was carried out using Kettell's personal 16-factor questionnaire and the test questionnaire «Subjective alienation of educational work» (V.N. Kosyrev). The obtained results demonstrate the existence of a relationship between the alienation of students with disabilities from educational activities and such character traits as adequate self-esteem, intelligence, emotional instability, courage, sensitivity, dreaminess, conformity, tension. The results can be used in the development of psychocorrective programs aimed at overcoming the alienation of students with the status of disabilities from educational activities.